The resurrection of God incarnate - Swinburne, Richard (oxford clarendon press, 2003)
Whether or not Jesus rose bodily from the dead is perhaps the most critical and contentious issue in the study of Christianity. Rather than depend on statements in the New Testament, Swinburne argues for a wider approach.
Introduction -- Part I: General Background Evidence -- 1. Principles for weighing evidence -- 2. God's reasons for Incarnation -- 3. The life required of an incarnate God -- Part II: Prior Historical Evidence -- 4. The Historical Sources -- 5. The life and moral teaching of Jesus -- 6. Jesus implied his divinity -- 7. Jesus taught his atonement -- 8. Jesus founded a church -- Part III: Posterior Historical Evidence -- 9. The appearance of the risen Jesus -- 10. The empty tomb, and the observance of Sunday -- 11. Rival theories of what happened -- 12. The significance of the Resurrection -- Part IV: Conclusion -- 13. The Balance of Probability -- Appendix: Formalizing the argument Index.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Resurrection; Philosophy and religion